Fact, fiction, and fairness: resource allocation under the Ryan White CARE Act. - Martin, Erika G; Pollack, Harold A; Paltiel, A David (Health affairs (Project Hope), 2006)
Debate over the reauthorization of the Ryan White CARE Act (RWCA) raises questions of fairness, equity, and efficiency. Critics charge that the program targets disproportionate resources to historical urban epicenters at the expense of underserved areas of incident HIV infection. We used 1998-2004 data on RWCA allocations to examine these claims. We found that states' concentration of AIDS cases within urban areas remains the dominant predictor of RWCA funding, although the impact of concentration declined after 2000. Other state characteristics, such as poverty rates or racial/ethnic diversity, play a much smaller role.
Keywords: Geography; Health Services Accessibility; HIV Infections; Humans; Medically Underserved Area; Poverty Areas; Program Development; Program Evaluation; Quality of Health Care; Questionnaires; Resource Allocation; Social Justice; United States; United States Health Resources and Services Administration; Urban Health Services